Comprehensive analysis of PD-L1 expression in glioblastoma multiforme - Heiland, Dieter Henrik; Haaker, Gerrit; Delev, Daniel; Mercas, Bianca; Masalha, Waseem; Heynckes, Sabrina; Gäbelein, Annette; Pfeifer, Dietmar; Carro, Maria Stella; Weyerbrock, Astrid; Prinz, Marco; Schnell, Oliver (Oncotarget, 2017)
Glioblastoma multiforme are highly malignant brain tumours with frequent genetic and epigenetic alterations. The poor clinical outcome of these tumours necessitates the development of new treatment options. Immunotherapies for glioblastoma multiforme including PD1/PD-L1 inhibition are currently tested in ongoing clinical trials. The purpose of this study was to investigate the molecular background of PD-L1 expression in glioblastoma multiforme and to find associated pathway activation and genetic alterations. We show that PD-L1 is up-regulated in IDH1/2 wildtype glioblastoma multiforme compared to lower-grade gliomas. In addition, a strong association of PD-L1 with the mesenchymal expression subgroup was observed. Consistent with that, NF1 mutation and corresponding activation of the MAPK pathway was strongly connected to PD-L1 expression. Our findings may explain different response to PD-L1 inhibition of patients in ongoing trials and may help to select patients that may profit of immunotherapy in the future.
CRIS-Team Scopus Importer:2023-09-13
Keywords: Glioblastoma multiforme; Immunotherapy; Integrative analysis; PD-L1; WGCNA